2011
DOI: 10.5935/1678-9741.20110044
|View full text |Cite
|
Sign up to set email alerts
|

Preditores de transfusão de concentrado de hemácias em cirurgia de revascularização miocárdica

Abstract: Preditores de transfusão de concentrado de hemácias em cirurgia de revascularização miocárdicaPredictors of transfusion of packed red blood cells in coronary artery bypass grafting surgery Conclusions:The identification of these risk factors leads to better identification of patients with a grater probability of using blood, allocation blood bank resources and costeffectiveness use of blood products. Rev Bras Cir Cardiovasc 2011;26(4):552-8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…In a prospective, randomized and controlled trial, it has become evident the increased mortality risk associated to the transfusions of 1-2, 3-4, 5-6 and > 6 units of packed red blood cells after cardiac surgery [ 11 ] . In the literature, there are other studies [ 15 , 20 ] , which have also shown adverse clinical outcomes by the amount of PRBCs associated effect. Our study has shown the isolated adverse effect of every allogeneic PRBCs unit transfused in the patient's population after one year of CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective, randomized and controlled trial, it has become evident the increased mortality risk associated to the transfusions of 1-2, 3-4, 5-6 and > 6 units of packed red blood cells after cardiac surgery [ 11 ] . In the literature, there are other studies [ 15 , 20 ] , which have also shown adverse clinical outcomes by the amount of PRBCs associated effect. Our study has shown the isolated adverse effect of every allogeneic PRBCs unit transfused in the patient's population after one year of CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In another study it has become evident that a more conservative blood transfusion approach, in cardiac surgery with CPB, it does not alter the mortality rate among the groups of restrictive strategy (hematocrit ≥ 24%) and liberal strategy (hematocrit ≥ 30%) [ 11 ] . It is already known that patients with hematocrit below 40%, and need for cardiopulmonary bypass and multiple bypasses, have a greater likelihood to use blood in CABG surgery, therefore, to identify, treat and/or prevent these conditions will result in less use of blood products transfusion [ 20 ] . Souza & Braile [ 24 ] demonstrated that a hemoconcentration during the CPB associated to a reduced water balance, is also able to decrease the use of blood and plasma in cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%